(untitled) (The Research of Medical Science Review, 2025)
Endotracheal extubation often triggers significant hemodynamic responses due to sympathetic stimulation, leading to potential complications. This study compares the efficacy of lignocaine and dexmedetomidine in attenuating these responses. Fifty patients undergoing elective surgeries were randomized to receive either lignocaineor dexmedetomidine priorto extubation. Hemodynamic parameters, including heart rate (HR) and mean arterial pressure (MAP), were monitored. Results indicated that dexmedetomidine provided superior hemodynamic stability compared to lignocaine, suggesting its advantage in managing extubation-induced stress.